The potrayal of Kelantanese identity in Che Husna Azhari's fiction - Nur Izzati binti Mohd. Sapperi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The Kelantanese are always admired and to some extent, envied by other Malays because of their strong sense of belonging. This sense of belonging is seldom portrayed in Malaysian English writing. However, Che Husna Azhari has taken the challenge to write on the uniqueness of regional Malay identity. The purpose of this thesis is to examine the portrayal of Kelantanese identity in Che Husna Azhari's short story collections, The Rambutan Orchard (1993a) and Melor in Perspective (1993b). Nine short stories have been selected by the researcher from these two volumes. The short stories portray the expression and the retainment of Kelantanese identity within and outside their community, notwithstanding migration and modernisation. This study is also intended to see the way culture, religion and gender mould the Kelantanese identity. It has been concluded that the Kelantanese people have gradually changed their identity by adapting to other cultures as well as the result of migration and modernisation. However, they are capable of maintaining their Kelantanese identity by conversing in the dialect in their daily conversation. Islam is the strongest identity marker for the Kelantanese people as it is embedded in most of their affairs. Nevertheless, the identity of the Kelantanese women has asserted a strong influence on the family, maintaining a strong sense of femininity at the same time. The clash between the pre-Islamic elements and Islam which prevails within the Kelantanese culture, is also a part of the identity of its people.